Developmental language disorders and special educational needs: consideration of inclusion in the Norwegian school context - Chahboun, Sobh; Wahl, Hilde T.; Langner, Jana; Vaags, Agnete (Frontiers in Education, 2024)
Children with language disorders face different challenges in their daily school routines.Accessing tools and having resources promoting a well-structured and inclusive environment is necessary to ensure a pleasant and successful passage through primary school.The current article seeks to highlight stimulating ideas, creating a foundation for involving everyone caring for and educating students with language disorders, particularly children with special needs. Moreover, experts need to prioritize educational initiatives aimed at language disorders, particularly emphasizing early detection, prevention, and specialized care.Balancing the need for students to get adequate attention while avoiding unequal treatment can be as difficult as dealing with a two-sided coin. Moreover, it is crucial to acknowledge that academic research should prioritize finding the best ways to support students with special needs who have language impairments. All professionals working with these students, such as speech therapists, psychopedagogical experts, and general therapists, need to focus on developing interventions and options to aid in their growth.